2020
DOI: 10.3390/s20030687
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Closed-Loop Sense MEMS Disk Resonator Gyroscope Circuit Design Based on Integrated Analog Front-end

Abstract: A digital closed-loop system design of a microelectromechanical systems (MEMS) disk resonator gyroscope (DRG) is proposed in this paper. Vibration models with non-ideal factors are provided based on the structure characteristics and operation mode of the sensing element. The DRG operates in force balance mode with four control loops. A closed self-excited loop realizes stable vibration amplitude on the basis of peak detection technology and phase control loop. Force-to-rebalance technology is employed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The input range and scale factor nonlinearity of the gyroscope are ±400°/s, 6.2 mV/°/s, and 0.035% respectively. More circuit design details and experimental data are described in our previous work [ 49 ]. In the experiment, we chose whether or not to use a chopping technique on the bandage reference in the drive loop (the reference voltage of the dive loop is generated by the reference voltage).…”
Section: Resultsmentioning
confidence: 99%
“…The input range and scale factor nonlinearity of the gyroscope are ±400°/s, 6.2 mV/°/s, and 0.035% respectively. More circuit design details and experimental data are described in our previous work [ 49 ]. In the experiment, we chose whether or not to use a chopping technique on the bandage reference in the drive loop (the reference voltage of the dive loop is generated by the reference voltage).…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Ju et al reported an auto-tuning continuous-time BPSDM for capacitance signal detection of MEMS gyroscopes [ 8 ]. Similar interface circuits [ 2 , 9 , 10 ] differ mainly in C/V converter and ADC. In the field of inertial measurement, interface ASIC based on capacitance detection continue to improve performance in terms of noise floor, dynamic range, and signal-to-noise ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Implementing signal processing algorithms on a Field Programmable Gate Array (FPGA) at the circuit level can solve the above problems and become a mainstream solution. In related works [ 7 , 10 , 13 , 14 , 15 , 16 ], the researchers reported their cases of signal measurement and control based on FPGA in the field of inertial measurement. When the digital signal processing circuits are designed and manufactured using integrated circuit technology, it can obtain performance beyond the FPGA solutions, which are also reported in some products [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous improvement of performance, it will excel in high-end applications such as navigation, defense, aviation and aerospace [ 1 , 2 ]. Recently, high performance gyros such as the frame type [ 3 , 4 , 5 , 6 , 7 ], the disc type [ 8 , 9 , 10 , 11 , 12 ], the butterfly [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], etc. have attracted a lot of attention from academia and industry.…”
Section: Introductionmentioning
confidence: 99%